"Time-varying model" and macroscopic / microcosmic mechanism analysis based on corroded steel mechanical property of bridge durability. (11th June 2018) - Ding, Zeng; Qihui, Zeng; Baohong, Hao; Jin, Zhao; Yuchen, Tang
ABSTRACT: In order not to get bridges collapsed instantaneously, this paper introduces the degradation laws of mechanical performance of corroded steel by making use of different electrochemical detections (by electrochemical detection, the features of corroded steel could be obtained quickly) and finite element analysis. Then according to the laws, this paper sets up "time-varying model" for the situation that carrying capacity changes because part of the bridge suffers corrosion. By the "time-varying model", a scientific deduction on the remained service life can be made. In this way, a relatively accurate forecast on the durability of bridges being used can be achieved. First, by a orthogonal test where the simulated corrosion is sped up, a relationship between electrochemical signal and corrosion ratio was established; second, by finite element analysis, a relation model between the steel corrosion and steel deformation obtained by electrochemical detection. By linking "potential signals -corrosion degree – deformation degree" and detecting the crystal microstructure of corrosion section, macroscopic deformation and microstructure of the materials were correlated. Then, under a complicated stress, this paper introduces the emergency response system and evolution mechanism of the corroded steel. By setting up a time-varying model involving "electrochemical signals – corrosion degree- deformation degree", a fast diagnosis system based on electrochemical signal is formed. Depending on such a diagnosis system, a forecast system to predict the durability of the bridges being used can be made, which is similar to the medical judgment that someone's lifetime or age can be predicted by the bone age. Then pursuant to the forecast, we can prevent crises before they emerge.